Defining “Adequately Treated”: A Post Hoc Analysis Examining Characteristics of Patients with Schizophrenia Successfully Transitioned from Once-Monthly Paliperidone Palmitate to Once-Every-3-Months Paliperidone Palmitate - O'Donnell A (Dove Medical Press, 2021)
Amy O’Donnell,1 Sanjai Rao,2 Ibrahim Turkoz,3 Srihari Gopal,3 Edward Kim1 1Janssen Scientific Affairs, LLC, Titusville, NJ, USA; 2Department of Psychiatry, University of California, San Diego, La Jolla, CA, USA; 3Janssen Research and Development, LLC, Titusville, NJ, USACorrespondence: Ibrahim TurkozJanssen Research and Development, LLC, Titusville, NJ, USATel +1 609-730-7719Fax +1 609-730-3232Email iturkoz@its.jnj.comPurpose: Paliperidone palmitate once every 3 months (PP3M) is indicated in adults with schizophrenia adequately treated with once-monthly paliperidone palmitate (PP1M) for at least 4 months, in whom the last two consecutive doses are the same. The decision of when to transition to PP3M is based on the patient’s symptom status while receiving PP1M.Patients and Methods: In a double-blind relapse–prevention study (NCT01529515), patients who met Positive and Negative Syndrome Scale (PANSS) score stabilization criteria after 4 months of PP1M were eligible for transition to PP3M; those who continued to meet stabilization criteria after 12 weeks following an open-label PP3M dose were randomized to receive PP3M or placebo. We compared (post hoc) PANSS, Clinical Global Impression–Severity (CGI-S), and Personal and Social Performance (PSP) scores during the pre-randomization, open-label phase in patients in randomized versus non-randomized groups using analysis of variance or chi-square tests.Results: Of 506 patients enrolled, 305 were randomized. After 4 months’ PP1M treatment, PANSS and CGI-S scores were significantly lower and PSP scores significantly higher in randomized patients versus non-randomized patients (least squares means [95% CI]: 57.1 [55.7, 58.6] vs 62.2 [60.0, 64.3], 2.9 [2.8, 3.1] vs 3.3 [3.1, 3.4], and 67.0 [65.7, 68.3] vs 64.5 [62.6, 66.4], respectively); changes from baseline between groups differed significantly (all P ≤ 0.009).Conclusion: Confirming adequate stabilization with PP1M prior to transitioning to PP3M is critical in maximizing treatment response; clinicians should consider transitioning patients to PP3M only if patients respond well to PP1M for at least 4 months and their last two consecutive doses are the same.Keywords: treatment outcome, administration and dosage, neuropsychiatric symptoms, psychosocial functioning, stabilization, long-acting injectable antipsychotic